2010
DOI: 10.1186/1465-9921-11-170
|View full text |Cite
|
Sign up to set email alerts
|

The laminin β1-competing peptide YIGSR induces a hypercontractile, hypoproliferative airway smooth muscle phenotype in an animal model of allergic asthma

Abstract: BackgroundFibroproliferative airway remodelling, including increased airway smooth muscle (ASM) mass and contractility, contributes to airway hyperresponsiveness in asthma. In vitro studies have shown that maturation of ASM cells to a (hyper)contractile phenotype is dependent on laminin, which can be inhibited by the laminin-competing peptide Tyr-Ile-Gly-Ser-Arg (YIGSR). The role of laminins in ASM remodelling in chronic asthma in vivo, however, has not yet been established.MethodsUsing an established guinea p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Various integrins have been implicated to modulate aspects of asthma pathophysiology - airway inflammation 7 , AWR 16 , and AHR 7 . Hence, it has been proposed that integrins are therapeutic targets in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Various integrins have been implicated to modulate aspects of asthma pathophysiology - airway inflammation 7 , AWR 16 , and AHR 7 . Hence, it has been proposed that integrins are therapeutic targets in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Dekkers et al (21) showed that exogenous laminin sustains a contractile phenotype and prevents proliferation of bovine tracheal smooth muscle cells. Using a guinea pig model of chronic asthma to further explore the role of laminins in ASM remodeling in vivo , the researchers treated the animals with the specific soluble laminin competing peptide YIGSR and showed that YIGSR did inhibit allergen‐induced ASM accumulation (22). However, in contrast to their previous in vitro studies, soluble YIGSR promoted a hypercontractile phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Guinea pigs have also been sensitized systemically to OVA by using alum as an adjuvant and were subsequently challenged with OVA aerosol for up to 12 weeks, which resembles protocols from mouse models of chronic experimental asthma. Such a protocol results in profound allergic airway inflammation associated with goblet cell hyperplasia, mucus gland hypertrophy, smooth muscle layer thickening and increased collagen deposition (Dekkers et al 2010 ; Maarsingh et al 2011 ; Lucarini et al 2014 ).…”
Section: Animal Models In the Study Of Airway Remodelingmentioning
confidence: 99%